Strong hydrogen bonding wide bandgap single crystal for optical and electronic applications. (December 2019) - Bincy, I.P.; Jaisankar, S.N.; Pachamuthu, M.P.; Santhanaraj, D.; Prakash, D.; Ramkumar, V.
Highlights: A good quality, transparent organic crystal 3HAPTS was grown by solution growth method. The optical band gap was found to be 4.01 eV. Electrical properties and Z-Scan results reveals, as 3HAPTS could suitable for NLO area. Abstract: The present work deals with an investigation on the synthesis, crystal growth and characterization of an organic molecule named, as 3-hydroxyanilinium p-Toluenesulfonate (3HAPTS) for third order nonlinear optical and electronic applications. A high quality of organic single crystal was grown by slow evaporation solution technique (SEST) and the characterization result reveals that the strong hydrogen bonding and interaction between the molecule. The FT-IR and NMR analyses were reveals that the confirmation of the functional group in the molecule. Thermal property of the material was investigated by Thermogravimetric analysis (TGA). The optical properties such as absorption and emission were studied through the UV–visible and fluorescence spectrophotometer. The wide bandgap energy of 3HAPTS calculated from the Kubelka-Munk function, and it was found to be 4.01 eV. The dielectric property, hardness and the mechanical behavior of the single crystal was done with Vicker's microhardness test. The third order nonlinear optical behavior of 3HAPTS was analyzed by Z-scan analysis.